ANALISIS HUBUNGAN ANTARA PERBUATAN PELANGGARAN (FRAUD) PERBANKAN DENGAN PRINSIP KEPERCAYAAN (FIDUCIARY RELATION PRINCIPLE) SESUAI PASAL 29 AYAT (4) UNDANG-UNDANG PERBANKAN NOMOR 10 TAHUN 1998 - Andreas Andrie Djatmiko; Imam Sukwatus Sujai (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2017)
Fraud represent a deed contempt of court (illegally), conducted by individual in and also outside organization, on the basis of intention or intention, as a mean to profit organization and also individual executing the action and can result incidence of a loss materially and also non- natural material by institution or company of banking specially. Categorize collision (such fraud) here conducted collision intentionally to procedure and also standard and or code of ethics, including but do not limited to collision having the character of criminal like transgression of crime and or regulation of banking of which can cause, almost cause or have caused loss of material and non-material to client or bank and or either through indirect or direct able to give advantage to worker, worker family or other third party. Application of number code/law 10 of 1998 as change of number code/law 7 on 1992 on banking expected to be able to give rule of law to itself bank and also client. To depositor client and also lender to get protection of adequate law and to bank alone is to realize stable and healthy banking system. Mentioned in Chapter of V number code/law 10 of 1998 about Construction and Observation, section 29 sentence (4) in giving credit and conduct other business activity, bank is obliged to go through the way of harmless of bank and importance of client entrusting its fund to bank.